STUDY ON PHARMACOTHERAPY OF NATURAL INGREDIENTS (TOGA) AS GASTRITIS THERAPY IN STUDENTS OF IBRAHIMY 1 SUKOREJO VOCATIONAL SCHOOL SITUBONDO - gasim soka, burhanudin; Nur Diana Kholidah (Poltekkes Kemenkes Medan, 2024)
Family Medicinal Plants (TOGA) are nutritious plants planted in yards and fields and managed by families. The types of plants grown fulfill the family's need for traditional medicines that can be made by themselves. The medicinal plants chosen are usually plants that can be used for first aid. The presence of medicinal plants in the home environment is very important, especially for families who do not have easy access to medical services such as clinics, health centers or hospitals. Each family can cultivate medicinal plants independently and use them so that the principle of independence in family medicine will be realized. Objective: to know the natural ingredients used to treat gastritis. Knowing the effectiveness of using natural ingredients as gastritis therapy, knowing the side effects of natural ingredients as gastritis therapy. Design: This research is descriptive research, namely literature review. Results: TOGA which has pharmacotherapeutic effects and is effective in treating gastritis is meniran, ginger, turmeric, ginger, white ginger, cinnamon, nutmeg. The average side effect of TOGA as a gastritis therapy is stomach ache.